The relationship of asthma with physical fitness of Junior High School students in Yogyakarta. - Isri Muninggar, Isri Muninggar (Universitas Gadjah Mada, 2002)
Background: The understanding on asthma and the patients daily quality of life remain an issue which still need to be elucidated. Information about the relationship between asthma and physical fitness is an important factor that has to be considered in the management of asthma patients.Objective: To examine the relationship between asthma and the physical activity and physical fitness, with regards to the factors influencing them, in junior high students in Yogyakarta.Research design: crosss sectional.Materials and Methods: The samples were part of a main research project on the prevalence of asthma in the population of junior high school students in Yogyakarta. The incidence of asthma was determined using a previously validated modified questionnaire from ISAAC, ATS 78 and Robertson. Cases were students diagnosed as asthma, and the controls were students without asthma. Cases and controls were matched for age, sex, and school year. The basic characteristics of the students and parents, daily circle activities, history of smoking, school grade and physical exercise, the time needed to run a 100 meters distance were obtained using a quesionnaire. Lung function tests were done before and after 10 minutes static bicycle exercise. Data are analyzed using student T-test and X2 test.Results: There were 219 students who fulfilled the inclusion criteria, consisted of 102 males (46.57%) and 117 females (53.43%). The case group (asthma) comprised 119 students while 100 students were the control group. There is no statistically significant difference between the average age of subjects in the case group (14.70 years) with the control group (14.62 years) (p=0.416). There were no statistically significant differences between the cases and controls concerning the school grade and physical exercise (p=0.243), the time needed to run 100 meters distance (p=0.959), daily activities, physical activities: athletic (p=0.511), game playing sport (p =0.342), bicycling (p =0.212), swimming (p=0.586), the ability to joint to physical activities/physical exercise. We also could not find statistically significant differences in the lung function test before: VC p=0.271, FVC p =0.694, FEV1 p=0.995, FEV1/FEC p=0.579, PEF 25% p=0.144, PEF 25-75% p=0.179, MVV p=0.340 and Ex. Time p=0.100, and after exercise using static bicycle for 10 minutes VC p=0.347, FVC p=0.805, FEV1 p=0.767, FEV1/FEC p=0.401, PEF 25% p=0.152, PEF 25-75% p=0.210, MVV p =0.310.Conclusion: There is no statistically significant difference in daily physical activities and school physical exercise activity between students in the asthmatic group and control group.Key words: Asthma physical fitness - physical activity - incidence of smoking - nutritional status - growth and development - lung function test